2021
DOI: 10.1177/00224278211001566
|View full text |Cite
|
Sign up to set email alerts
|

Foster Care, Permanency, and Risk of Prison Entry

Abstract: Objective: (1) Examine associations of foster care exit type (e.g., reunification with birth family, adoption, guardianship/permanent relative placement, or emancipation from care) with risk of entry into state prison; (2) Examine racial disparities in those associations. Method: With data on over 10,000 Wisconsin youth who entered foster care in mid- to late-childhood, we present imprisonment rates in young adulthood by race, sex, and foster care exit type. Proportional hazards models with a robust set of cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…Traditional criminological theories would arguably suggest that permanency is consistent with reducing crime and delinquency because emancipation implies a lack of a permanent committed caregiver and often follows unstable living arrangements while in care, including more frequent changes in schools and neighborhoods, which the reduces potential for other stable prosocial influences. However, that study of several thousand youth entering foster care in Wisconsin found a higher risk of prison entry for reunified youth, in both bivariate analyses and multivariate analyses accounting for differences in settings and experiences within foster care (Font et al 2021). Although that study was based on a single state, their findings align with other research indicating that reunification from foster care may increase juvenile justice involvement ( Jonson-Reid & Barth 2000) and behavioral problems (Bellamy 2008).…”
Section: Beyond Average Effects Of Foster Caresupporting
confidence: 74%
See 2 more Smart Citations
“…Traditional criminological theories would arguably suggest that permanency is consistent with reducing crime and delinquency because emancipation implies a lack of a permanent committed caregiver and often follows unstable living arrangements while in care, including more frequent changes in schools and neighborhoods, which the reduces potential for other stable prosocial influences. However, that study of several thousand youth entering foster care in Wisconsin found a higher risk of prison entry for reunified youth, in both bivariate analyses and multivariate analyses accounting for differences in settings and experiences within foster care (Font et al 2021). Although that study was based on a single state, their findings align with other research indicating that reunification from foster care may increase juvenile justice involvement ( Jonson-Reid & Barth 2000) and behavioral problems (Bellamy 2008).…”
Section: Beyond Average Effects Of Foster Caresupporting
confidence: 74%
“…A renewed emphasis on testing mechanisms and heterogeneity in foster care effects is especially urgent for two reasons. First, the subgroup of children with high levels of emotional and behavioral disturbance (those at greater risk for crime and delinquency) are the least likely to have positive experiences in foster care-less stability, more time in congregate care (versus nonrelative family or kinship foster care), and lower rates of permanency through adoption or guardianshipwhich may augment risks of crime and delinquency (Font et al 2021, Ryan et al 2008, Ryan & Testa 2005. Second, foster care objectives are poorly aligned with, or contrary to, strategies for preventing crime and delinquency, despite the CWS goals of safety, permanency, and wellbeing seeming to be consistent with delinquency prevention.…”
Section: Beyond Average Effects Of Foster Carementioning
confidence: 99%
See 1 more Smart Citation
“…Department of Health and Human Services, 2020). Given large and persistent racial disparities in neighborhood disadvantage (Reardon et al, 2015), income and wealth, and family structure (McLanahan & Percheski, 2008), racial disparities in outcomes may be larger after discharge than within foster care as children are placed in environments with vastly different resources (Font et al, 2021). Our analysis does find some evidence that gaps in negative outcomes are larger for Black FCIPs than White FCIPs in studies of minors who have exited foster care than in studies of individuals in foster care at the time of outcome measurement, but it is based on a small number of studies.…”
Section: Discussionmentioning
confidence: 99%
“…The scoping review and interviews suggested that learning losses occur when schools are closed for lengthy periods of time, and this was supported by foster parent responses on the survey. Since children and youth come into foster care lagging behind educationally (Font et al, 2021 ; Sullivan et al, 2010 ; Vacca, 2008 ), COVID-19 school closures had the potential to widen the learning gap. Despite concerted efforts by foster parents and teachers, foster parents reported that engaging youth in foster care with online learning was very challenging.…”
Section: Resultsmentioning
confidence: 99%